DIGITAL TRANSFORMATION IN HEALTHCARE REHABILITATION: A NARRATIVE REVIEW - AFRIDI, Ayesha; NAWAZ KHAN, Shah (Journal of process management and new technologies, 2024)
The incorporation of digital technologies into healthcare rehabilitation is fundamentally changing patient care. This narrative study is aimed to explore the changing landscape of digital transformation in healthcare rehabilitation, concentrating on the skills and training needed for healthcare professionals, as well as their impact on patient outcomes. The narrative review progresses by delving into the history of healthcare rehabilitation, the growing role of digital technology, and their impact on rehabilitation methods. It defines the important areas of effect, goes into the applications of digital technology, and dissects the abilities required of healthcare professionals, classifying them as technical, soft, and cognitive. The review emphasizes the importance of interprofessional collaboration and skill exchange among healthcare professionals and technology. Furthermore, empirical evidence is used to examine the direct relationship between the adoption of digital technologies and patient outcomes. Ethical concerns, regulatory barriers, and efforts to bridge the digital gap and improve accessibility are explored. The narrative continues by highlighting the impact of these findings on healthcare professionals, institutions, and policymakers, and highlighting the importance of this research in the ongoing era of digital transformation.
Keywords: Digital Transformation; HealthCare; AI; Virtual Reality (VR); Telemedicine